2020
DOI: 10.3389/fmolb.2020.00186
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Targeting Approach to Fight SARS-CoV-2 Attachment

Abstract: The public health has declared an international state of emergency due to the spread of a new coronavirus (SARS-CoV-2) representing a real pandemic threat so that to find potential therapeutic agents is a dire need. To this aim, the SARS-CoV-2 spike (S) glycoprotein represents a crucial target for vaccines, therapeutic antibodies, and diagnostics. Since virus binding to ACE-2 alone could not be sufficient to justify such severe infection, in order to facilitate medical countermeasure development and to search … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 27 publications
0
29
0
Order By: Relevance
“…of the spike glycoprotein do not preclude additional effects of chondroitin sulfates and proteoglycans in the pathophysiology of Covid-19 [19][20][21][22][23]. Identification of a galectin-like fold in the spike glycoprotein suggests that additional interactions with β-galactosides may contribute to binding of SARS-CoV-2 to cell surfaces [24][25][26][27][28]. Clausen et al reported that in A375 cells in which ACE2 was overexpressed, knockout of B4GALT7 (beta-1,4-galactosyltransferase 7), a gene required for proteoglycan and GAG assembly, reduced the binding of the spike glycoprotein [21].…”
Section: Interactions Between Heparin and Heparan Sulfate And The Recmentioning
confidence: 99%
See 1 more Smart Citation
“…of the spike glycoprotein do not preclude additional effects of chondroitin sulfates and proteoglycans in the pathophysiology of Covid-19 [19][20][21][22][23]. Identification of a galectin-like fold in the spike glycoprotein suggests that additional interactions with β-galactosides may contribute to binding of SARS-CoV-2 to cell surfaces [24][25][26][27][28]. Clausen et al reported that in A375 cells in which ACE2 was overexpressed, knockout of B4GALT7 (beta-1,4-galactosyltransferase 7), a gene required for proteoglycan and GAG assembly, reduced the binding of the spike glycoprotein [21].…”
Section: Interactions Between Heparin and Heparan Sulfate And The Recmentioning
confidence: 99%
“…Recent studies have implicated these GAGs in viral attachment of the receptor binding domain (RBD) of the spike glycoprotein to the angiotensin converting enzyme 2 (ACE2) receptor in mammalian cells [21][22][23]. A galectin-like fold has been identified in the N-terminal domain of the spike protein of SARS-CoV-2, resembling similar structures in other coronaviruses [24][25][26][27][28]. The presence of this fold suggests potential binding with cell-based galactosides, such as those of chondroitin sulfates, which are the preferred binding partners of galectins.…”
Section: Introductionmentioning
confidence: 95%
“…Computational studies suggest that the RGD-motif is not per se accessible for integrin binding, but it only becomes exposed following proteolytic processing and the associated conformational changes within the spike protein after SARS-CoV-2 binding to ACE2 [ 480 , 481 ]. Interestingly, ACE2 also displays a conserved RGD-motif, potentially available for integrin binding and the enhancement of cell adhesion and thus increased infectivity [ 482 ]. However, previous studies already showed that this RGD-motif within ACE2 is inaccessible and would require either a conformational shift to be exposed or an RGD-independent binding mechanism.…”
Section: Integrin Targeting In Non-cancer Diseasesmentioning
confidence: 99%
“…Currently, the entire world is under a threat of Covid-19 (β-coronavirus or group-2) infection which was emerged in Wuhan, China during December 2019. From genetic studies, it was found that bats are the primary sources and considered as hosts for the strains of viruses such as SARS-CoV and MERS-CoV before spreading to humans (Pirone et al, 2020).…”
Section: Sars-cov-2: Genomic Structure and Pathogenesismentioning
confidence: 99%